1991
DOI: 10.1515/jpme.1991.19.5.357
|View full text |Cite
|
Sign up to set email alerts
|

Fetal urinary tract obstructions: Prenatal diagnosis — prenatal and postnatal therapy

Abstract: A retrospective study was conducted comprising 78 cases of fetal urinary tract obstructions diagnosed by ultrasound. Thirteen of the obstructions were subvesical and 65 supravesical. In only one fetus with a subvesical obstruction leading to megacystis was a puncture of the fetal bladder performed--in the 17th week of gestation--resulting in restitution of the bladder to its normal size. In all of the remaining fetuses the kidneys, lungs, and bladder changes had already reached an advanced stage by the time th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…However, the hydronephrotic type of multicystic dvplastic kidney was mainly composed of a single large cyst and it would be difficult to distinguish it from severe hydronephrosis by an ultrasonographic examination alone [21], The remaining 5 cases showed regional variations in the af fected sites between the antenatal and postna tal diagnoses. Similar discrepancies have also been found in the literature [1,7,16], The rea sons for this might not solely be due to techni cal problems. In other words, it is considered that this phenomenon indicates one of the important characteristics of fetal uropathy.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, the hydronephrotic type of multicystic dvplastic kidney was mainly composed of a single large cyst and it would be difficult to distinguish it from severe hydronephrosis by an ultrasonographic examination alone [21], The remaining 5 cases showed regional variations in the af fected sites between the antenatal and postna tal diagnoses. Similar discrepancies have also been found in the literature [1,7,16], The rea sons for this might not solely be due to techni cal problems. In other words, it is considered that this phenomenon indicates one of the important characteristics of fetal uropathy.…”
Section: Discussionsupporting
confidence: 82%
“…By 25 weeks, it is possible to distinguish the cortex from the medulla, to define the renal outline and to see a central echo [15], The gestational age at diagnosis was 29.6 ± 5.8 weeks (range 8-38 weeks) in the present study and this figure was similar to that of Tam et al [12] (27 ± 7 weeks, range 16-39 weeks). In a report on obstructive uropathy by Wilhcm et al [16], the peak age at the time of detection was found to be around 35 weeks of gestation [ 16], In the present series, only 3 cases were de tected before the 20th gestational week (5%), and they were complicated cases with other anomalies than the urinary system. The ear liest one was a case of prune belly syndrome, detected by megaeystis at 8 gestational weeks.…”
Section: Discussionsupporting
confidence: 40%
“…Of the initial articles selected on title and abstract, 107 were excluded because they did not meet the selection criteria (Figure 1). A further 10 articles (7.5% of original articles selected) were felt to contain relevant data and the authors were contacted 6,12,35–42 . One of these provided the original dataset and was included 12 .…”
Section: Resultsmentioning
confidence: 99%
“…A further 10 articles (7.5% of original articles selected) were felt to contain relevant data and the authors were contacted. 6,12,[35][36][37][38][39][40][41][42] One of these provided the original dataset and was included. 12 The final dataset included 13 articles, with a total of 215 women and 33 2 · 2 tables.…”
Section: Data Synthesismentioning
confidence: 99%